Regenerative Effects of Three Types of Allografts on Rabbit Calvarium: An Animal Study - Amir Reza Rokn; Abbas Seyed Shakeri; Shahroo Etemad-Moghadam; Mojgan Alaeddini; Ahmad Reza Shamshiri; Rebecca Manasheof; Hamidreza Barikani (Tehran University of Medical Sciences, 2016)
Objectives: The aim of this study was to histologically compare the regenerative properties of two allografts manufactured by two Iranian companies. Materials and Methods: In this study, four 8-mm defects were produced in the calvaria of 12 rabbits. In three defects, three types of allografts namely ITB, CenoBone and Grafton were placed and one defect served as control. Samples were prepared and histomorphometric evaluations were carried out after healing periods of four weeks (interval 1) and eight weeks (interval 2). Qualitative and quantities variables were compared and analyzed with SPSS software. Results: Mild inflammation was observed in 45% and 12.5% of the samples in the first and second intervals, respectively. Foreign body reaction was observed in only 5% of the samples. The quality of regenerated bone was immature, mixed and lamellar in 54.5%, 15.9% and 4.5% of the samples, respectively. The rate of allograft resorption was the highest and lowest in the CenoBone and Grafton samples, respectively. The mean amount of regenerated bone was higher in areas containing Grafton; however, the differences were not statistically significant. Conclusion: Despite the differences in the numerical values of bone regeneration, there were no statistically significant differences in bone generation among the material groups, and allografts manufactured in Iran can be suitable alternatives to Grafton with the same good properties. Further studies are necessary to clarify the efficacy of these allografts.